Analisis Du Pont dalam Mengukur Kinerja Keuangan Perusahaan MICE di Indonesia (Studi Kasus pada PT Dyandra Media International Tbk) - Asterina Anggraini; Firman Syah (Bisnis Event, 2023)
This study aims to measure the financial performance of PT Dyandra Media International, which is a company engaged in the MICE business in Indonesia for the period 2014 to 2021 using du pont analysis. Based on du pont analysis, the ratios used are net profit margin, total assets turnover, return on assets, equity multiplier, and return on equity. By using quantitative descriptive methodology, the largest return on equity ratio occurred in 2018. This is because the return on assets ratio and equity multiplier ratio in 2018 are quite high. Throughout 2018, all strategies were successfully implemented by the company so that it had an impact on increasing profits in 2018. This increase in profit was not only influenced by the sale of hotel assets and increased operating income as well as consistent efficiency and cost control in various aspects in all business units.